Effect of Rotation Speed of a Friction Pair on Transmission Characteristics of a Rotating Oil Film - Xie, Fangwei; Xuan, Rui; Sheng, Gang; K. Agarwal, Ramesh (Recent Patents on Mechanical Engineering, 2015)
In order to analyze the effect of rotation speed of a friction pair on transmission characteristics of a rotating oil film, a 3D computational model of an oil film between a friction pair is built; pressure, temperature, velocity, and torque transferred by the rotating oil film are investigated at rotation speeds of 1000r/min, 3000r/min, and 4000r/m using the computational fluid dynamics (CFD) software ANSYS Fluent. It is found that the highest pressure in the oil film decreases with increase in rotation speed and its value decreases gradually along the radial direction. However, the distributions of velocity and temperature are opposite to that of the pressure; the highest value of these quantities appears at the outer radius. The torque, which is proportional to the rotation speed, is also calculated theoretically and is compared with the CFD simulation results. The purpose of this study is to provide an overview about the effect of rotation speed of a friction pair on transmission characteristics of oil film by addressing recent patents and scholarly articles on the subject of design, control and application of such systems.
Keywords: transmission characteristics